Financial management practices and level of financial stress of business school's faculty member in Pamantasan ng Lungsod ng Maynila - Borja, Ashley H., Dizon, Angeline C., Santos, Janus F., Sierra, Crystal Kaye R., Toldedo, John Kenneth R., Zamora, Norielle C. 4 0 16; 5 (2023)
Abstract This study entitled, Financial Management Practices and Level of Financial Stress of Business School's Faculty Members in Pamantasan ng Lungsod ng Maynila was prepared by Borja, Ashley H. Dizon, Angeline C. Santos, Janus F. Sierra, Crystal Kaye R. Toledo, John Kenneth R. and Zamora, Norielle C. in partial fulfillment of the requirements for the subject Business Research. This was prepared under the supervision of Dr. Marivic F. Flores. The objective of the research is to determine the primary factors that impact the level of financial stress among faculty members. This extensive study spans over 60 pages and investigates the correlation between financial management practices, including saving habits, spending patterns, and debt management, and the degree of financial stress encountered by faculty members at the Business School of Pamantasan ng Lungsod ng Maynila. The researchers made use of the descriptive correlative method which involves the gathering of data using a physical contact survey and an online survey questionnaire through Google Forms. From 26 faculty members that are selected, there are only 19 respondents that answer our survey and 7 individuals chose to reject or unavailable at the given time. Out of the 19, 12 of them answered in Google Forms and 7 answered in the physical contact survey. The data was analyzed with the help of tools such as frequency, percentage, weighted mean, and pearson correlation coefficient. Based on the findings, it was discovered that there is no correlation between financial management practices and the level of financial stress among the Business School faculty members. Based on the study's findings, the researchers recommend that future researchers to input the civil status and the number of children on the demographic part of the survey questionnaire.
Research Paper; (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2